Alkaline Pretreatment of Sweet Sorghum Bagasse for Bioethanol Production - Sudiyani, Yanni; Triwahyuni, Eka; Muryanto, Muryanto; Burhani, Dian; Waluyo, Joko; Sulaswaty, Anny; Abimanyu, Haznan (International Journal of Renewable Energy Development, 2016)
Lignocellulosic material, which consist mainly of cellulose, hemicelluloses and lignin, are among the most promising renewable feedstocks for the production of energy and chemicals.   The bagasse residue of sweet sorghum can be utilized as raw material for alternative energy such as bioethanol.  Bioethanol production consists of pretreatment, saccharification, fermentation and purification process.  The pretreatment process was of great importance to ethanol yield.  In the present study, alkaline pretreatment was conducted using a steam explosion reactor at 1300C with concentrations of NaOH  6, and 10% (kg/L) for 10, and 30 min.  For ethanol production separated hydrolysis and fermentation (SHF) and simultaneous saccharification and fermentation (SSF) process were conducted with 30 FPU of Ctec2 and Htec2 enzyme and yeast of Saccharomyces cerevisiae.   The results showed that maximum cellulose conversion to total glucose plus xylose were showed greatest with NaOH 10% for 30 min.  The highest yield of ethanol is 96.26% and high concentration of ethanol 66.88 g/L were obtained at SSF condition during 48 h process. Using SSF process could increase yields and concentration of ethanol with less energy process. Article History: Received January 16th 2016; Received in revised form May 25th 2016; Accepted June 28th 2016; Available onlineHow to Cite This Article: Sudiyani, Y., Triwahyuni, E., Muryanto, Burhani, D., Waluyo, J. Sulaswaty, A. and Abimanyu, H. (2016) Alkaline Pretreatment of Sweet Sorghum Bagasse for Bioethanol Production. Int. Journal of Renewable Energy Development, 5(2), 113-118.http://dx.doi.org/10.14710/ijred.5.2.113-118